Primary Prophylaxis for High-Risk Varices in Patients with Hepatocellular Carcinoma and Portal Vein Tumor Thrombus Delayed Hepatic Decompensation: A Retrospective, Propensity Score Matching Study - Chen YJ; Hou MC; Yang TC; Lee PC; Lu HS; Huang HC; Huang YH; Luo JC (Journal of Hepatocellular Carcinoma, 2025)
Yu-Jen Chen,1– 3 Ming-Chih Hou,1– 3 Tsung-Chieh Yang,1– 3 Pei-Chang Lee,1– 3 Hsiao-Sheng Lu,1– 3 Hui-Chun Huang,1– 3 Yi-Hsiang Huang,2,4,5 Jiing-Chyuan Luo1– 3 1Division of Gastroenterology and Hepatology, Department of Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 2Healthcare and Services Center, Taipei Veterans General Hospital, Taipei, Taiwan; 3Therapeutic and Research Center of Liver Cirrhosis and Portal Hypertension, Taipei Veterans General Hospital, Taipei, Taiwan; 4National Yang-Ming Chiao-Tung University School of Medicine, Taipei, Taiwan; 5Therapeutic and Research Center of Liver Cancer, Taipei Veterans General Hospital, Taipei, TaiwanCorrespondence: Ming-Chih Hou, Division of Gastroenterology and Hepatology, Department of Medicine, Taipei Veterans General Hospital, No. 201, Sec. 2, Shih-Pai Road, Taipei, 112, Taiwan, Tel +886-2-2875-7506, Fax +886-2- 2873-9318, Email mchou@vghtpe.gov.twBackground and Aims: The prevalence of clinically significant portal hypertension (CSPH) is high in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombus (PVTT). There was no evidence of whether primary prophylaxis is beneficial in reducing hepatic decompensation in these patients.Methods: Clinical records of 445 patients with pathology or radiology-confirmed HCC and PVTT from January 2013 to December 2022 were reviewed, 142 patients having concurrent high-risk varices (HRV) without hepatic decompensation were enrolled. Patients were divided into the prophylaxis group and non-prophylaxis group. Propensity score matching was used for group comparison. The primary endpoint was decompensation-free survival (DFS), and the secondary endpoints were the incidence of esophageal variceal bleeding (EVB) and overall survival (OS).Results: The incidence of EVB was higher in the non-prophylaxis group than in the prophylaxis group (46.8% VS 21%, p = 0.001). DFS was longer in the prophylaxis group than in the non-prophylaxis group (84 days vs 66 days, p = 0.009). There was no difference in OS between two groups. In multivariate analysis, primary prophylaxis was associated with longer DFS (HR 0.806, p = 0.017); Immunotherapy (IO) was associated with longer DFS and OS; Barcelona Clinic Liver Cancer (BCLC) stage D was associated with shorter DFS and OS.Conclusion: Primary prophylaxis delays hepatic decompensation in HCC patients with PVTT. The incidence of EVB was also lower in the prophylaxis group, particularly in those treated with NSBB. First-line IO treatment is independently associated with better DFS and OS. Keywords: clinically significant portal hypertension, hepatocellular carcinoma, portal vein tumor thrombus, hepatic decompensation